THE SABBATH COMMANDMENTS IN EXODUS 20 AND DEUTERONOMY 5: COMPARATIVE STUDY - Kelendonu, Michael Andrew; Pasuhuk, Suryanica Aristas (Klabat Theological Review, 2024)
One of the fundamental ideas that guided the establishment of the Seventh-day Adventist Church movement was the Sabbath doctrine. In Exodus 20, the Israelites were explicitly given the mandate to observe the Sabbath holy. as a day of rest to honor the completion of creation by God. Verse 11 lists the reasons for keeping the Sabbath holy and commemorated, which are consistent with Genesis 2:2. Nevertheless, Deuteronomy 5 also has a comparable command. The Sabbath was instituted to remind people of their salvation and to allow them to reflect on their deliverance from slavery while they rested in the goodness of their God. Exodus 20:11 and Deuteronomy 5:15 complement each other when it comes to the reasons why the Sabbath should be kept, despite their discrepancies. The way the Ten Commandments are rephrased in Deuteronomy adds to the significance of the Sabbath. Consequently, rather than contradicting one another, these two passages reinforce one another. Keywords: Sabbath, salvation, slavery, commandments, Exodus, Deuteronomy